A New Wave of Mass Shootings? Exploring the Potential Impact of COVID-19. Issue 4 (November 2022) - Schildkraut, Jaclyn; Turanovic, Jillian J.
Although the COVID-19 pandemic has brought much of U.S. society to a grinding halt, its impact on the occurrence of mass shootings is largely unknown. Using data from the Gun Violence Archive and an interrupted time-series design, we analyzed weekly counts of mass shootings in the U.S. from 2019 through 2021. Results show that total, private, and public mass shootings increased following the declaration of COVID-19 as a national emergency in March of 2020. We consider these findings in the context of their broader implications for prevention efforts as well as how they pave the way for future research.